Melanoma metastatic to a ruptured silicone breast implant capsule - Mark J Wilsher; Nicholas J Moncrieff (Wolters Kluwer Medknow Publications, 2012)
Metastasis to the breast is rare and most commonly represents spread from a contra-lateral primary mammary carcinoma. Metastasis of solid non-mammary carcinoma is very rare and melanoma and neuro-endocrine bronchogenic carcinoma are the more common primary neoplasms implicated. In up to half of affected individuals, there may be no prior diagnosis of malignancy. Breast metastasis by melanoma to our knowledge has never been described to an augmented breast, moreover, to a ruptured implant capsule.